Penggunaan Vokatif Gelar Berpartikel /Y?/ dalam Bahasa Arab pada Buku /?al-qir??atu ‘r-raš?datu/: Kajian Sintaksis - Fathurrohim, Ilham Hanif; Wagiati, Wagiati; Kadir, Puspa Mirani (Humanis; Vol 28 No 2 (2024)DO - 10.24843/JH.2024.v28.i02.p04, 2024)
As in most languages, the Arabic vocative is a lingual unit that has an important position in communication, like showing politeness, familiarity, etc. This research aims to analyze the syntactic dimensions of the vocative title with the particle /y?/ in Arabic and was conducted to fill the research gap regarding the vocative title in Arabic. This research uses a mixed methods, with the book /?al-qir??atu ‘r-raš?datu/ as the data source. The data was analyzed using agih method with a syntactic approach, namely revealing the form of the particle /y?/ vocative title, the type of sentence that accompanies it, and its distribution in the sentence. The results show that the vocative title mostly uses the particle form /y?/ zhahir, used in news sentences, and at the beginning of sentences. It’s hoped that the results of this research can become a reference for Arabic learners to study and practice in daily communication